PEMAHAMAN TERHADAP RADIASI ALAM DAN PROTEKSI RADIASI PADA WARGA BUMI MAS CISEENG BLOK B5/05 KELURAHAN KURIPAN KECAMATAN CISEENG KAB BOGOR: UNDERSTANDING OF NATURAL RADIATION AND RADIATION PROTECTION ON CITIZENS BUMI MAS CISEENG BLOK B5/05 KURIPAN SUB-DISTRICT, CISEENG DISTRICT - Irsal, Muhammad (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2022)
Awareness and perception have become a public health and environmental problem for at least the last two decades, so public awareness and understanding of knowledge about natural radiation and radiation protection efforts are needed. The method by providing understanding is carried out by counseling using posters and interactive lectures, accompanied by the provision of pre-post test questionnaires to measure residents' understanding of radiation and the protection efforts that can be done. Then the data obtained will be tested using SPSS 26 to find out whether there is a change in understanding after providing counseling to residents with the Wilcoxon test. The results after the community knowledge counseling increased by 92% for indicators of understanding, utilization, and effects of radiation, while 97% for indicators of radiation protection with antioxidants. From the results of the Wilcoxon test, the p value < 0.001 therefore it can be said that counseling activities about radiation and protection efforts can affect the level of understanding of the residents.